2022
DOI: 10.3390/healthcare10010143
|View full text |Cite
|
Sign up to set email alerts
|

Poor Diet, Long Sleep, and Lack of Physical Activity Are Associated with Inflammation among Non-Demented Community-Dwelling Elderly

Abstract: Inflammation in elderly is associated with physical and cognitive morbidity and mortality. We aimed to explore the association of modifiable lifestyle parameters with inflammation among non-demented, community-dwelling elderly. A sub-sample of 117 patients with mild cognitive impairment (MCI, n = 63) and cognitively non-impaired controls (CNI, n = 54) were recruited from a large, population-based cohort in Crete, Greece, of 3140 elders (> 60 years old). All participants underwent assessment of medical histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
3
5
0
Order By: Relevance
“…Few studies have reported on associations between inflammatory markers and specific food groups [12,32,33], with a particular scarcity of data in the elderly population. Previously, reports have shown inverse relationships between biomarkers of inflammation in older adults and intakes of FV [17][18][19] and vegetables alone [34]. Our data revealed a significant impact of vegetables but not fruits on the levels of the inflammatory biomarker Il-6, which is in line with data showing inverse relationships between vegetable intake and IL-6 levels in middle-aged [33] and older adults [34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Few studies have reported on associations between inflammatory markers and specific food groups [12,32,33], with a particular scarcity of data in the elderly population. Previously, reports have shown inverse relationships between biomarkers of inflammation in older adults and intakes of FV [17][18][19] and vegetables alone [34]. Our data revealed a significant impact of vegetables but not fruits on the levels of the inflammatory biomarker Il-6, which is in line with data showing inverse relationships between vegetable intake and IL-6 levels in middle-aged [33] and older adults [34].…”
Section: Discussionsupporting
confidence: 91%
“…Previously, reports have shown inverse relationships between biomarkers of inflammation in older adults and intakes of FV [17][18][19] and vegetables alone [34]. Our data revealed a significant impact of vegetables but not fruits on the levels of the inflammatory biomarker Il-6, which is in line with data showing inverse relationships between vegetable intake and IL-6 levels in middle-aged [33] and older adults [34]. Our finding is further strengthened by the fact that adiposity level was accounted for in the present analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, other nutrients included in fruits act as co-factors for neurotransmitters, significant in mood regulation [ 47 ]. It has been also suggested that in older adults inflammation markers are connected with low fruit consumption [ 48 ]; thus, the association of fruits with depression may be explained through neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The sleep variables estimated were night sleep efficiency (SE), night wake after sleep onset time (WASO), night and 24-h total sleep time (TST) and finally, night and 24-h time spent in bed (TiB). Following our previous publication [34],…”
Section: Objective Sleep Measuresmentioning
confidence: 99%